2013
DOI: 10.1111/cdev.12191
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination and Ethnic Affirmation: Anglo Culture Orientation as a Moderator Among Mexican‐Origin Adolescent Mothers

Abstract: The current study examined whether Anglo culture orientation modified the association between adolescents’ perceived ethnic discrimination and ethnic identity affirmation over time in a sample of Mexican-origin adolescent mothers (N = 205, M age = 16.24 years). Results indicated that perceived ethnic discrimination was significantly associated with decreases in ethnic identity affirmation over time for adolescents reporting high Anglo culture orientation, but no relation existed for adolescents reporting low A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…As a recent example of this approach (Derlan et al, 2014) suggested that ERI would act as a protective mechanism against discrimination, whereby students would continue to engage in classroom learning despite the perception that their teachers discriminated against them. Note that in the absence of the perceived discrimination, no correlation between ERI and achievement would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…As a recent example of this approach (Derlan et al, 2014) suggested that ERI would act as a protective mechanism against discrimination, whereby students would continue to engage in classroom learning despite the perception that their teachers discriminated against them. Note that in the absence of the perceived discrimination, no correlation between ERI and achievement would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…This relation is consistent with prior work linking experiences of discrimination to more sleep disruptions, lower sleep quality, and fewer hours of sleep (Slopen et al, 2015), and suggests that, when youth are oriented only to Anglo culture, they are at a disadvantage as compared to their bicultural and enculturated counterparts. Being more exclusively oriented to the mainstream culture (acculturated) may make experiences of discrimination—which are likely coming from members of the mainstream culture—particularly harmful because they create dissonance and a sense of alienation (Derlan, eta l., 2014). However, if individuals’ cultural orientations encompass both the mainstream culture and their culture of origin, the impact of discrimination may be lessened because their bicultural orientation provides a second cultural group to turn to for affirmation and support.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cultural orientations may provide Mexican-origin young adults a lens through which to view and understand events; when they perceive discrimination, its meaning may be interpreted through their cultural orientation configuration. If individuals are strongly and more exclusively oriented to the mainstream culture, experiences of ethnic-based discrimination may be particularly harmful because they create dissonance and a sense of alienation: Although the individual's identity is strongly connected to the dominant culture, others treat them as cultural outsiders in ethnic-based discrimination (Derlan, Umaña-Taylor, Toomey, Updegraff, Jahromi, & Flores, 2014). However, if individuals’ cultural orientations encompass both the mainstream culture and their culture of origin, the impact of discrimination may be lessened because their bicultural orientation provides a second cultural group to turn to for affirmation and support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, extant studies on ethnic minorities' discrimination experiences have focused mainly on African Americans and Latinos (Derlan et al, 2014; Seaton et al, 2014; Seaton, Yip, & Sellers, 2009). There is a dearth of studies on the relationship between discrimination and adolescent outcomes, specifically ethnic identity, among Asian Americans (Umaña-Taylor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%